Generation and characterisation of gallium titanate surfaces through hydrothermal ion-exchange processes. (5th October 2018) - Wadge, Matthew D.; Stuart, Bryan W.; Thomas, Kathryn G.; Grant, David M.
Abstract: Infection negation and biofilm prevention are necessary developments needed for implant materials. Furthermore, an increase in publications regarding gallium (Ga) as an antimicrobial ion has resulted in bacterial-inhibitory surfaces incorporating gallium as opposed to silver (Ag). The authors present the production of novel gallium titanate surfaces through hydrothermal ion-exchange reactions. Commercially-pure Ti (S0: Cp-Ti) was initially suspended in NaOH solutions to obtain sodium titanate (S1: Na2 TiO3 ) layers ca. 0.5–1 μm in depth (2.4 at.% Na). Subsequent suspension in Ga(NO3 )3 (S2: Ga2 (TiO3 )3 ), and post-heat-treatment at 700 °C (S3: Ga2 (TiO3 )3 -HT), generated gallium titanate layers (9.4 and 4.1 at.% Ga, respectively). For the first time, RHEED analysis of gallium titanate layers was conducted and demonstrated titanate formation. Degradation studies in DMEM showed S2: Ga2 (TiO3 )3 released more Ga compared to S3: Ga2 (TiO3 )3 -HT (2.76 vs. 0.68 ppm) over 168 h. Furthermore, deposition of Ca/P in a Ca:P ratio of 1.71 and 1.34, on S2: Ga2 (TiO3 )3 and S3: Ga2 (TiO3 )3 -HT, respectively, over 168 h was seen. However, the study failed to replicate the antimicrobial effect presented by Yamaguchi who utilised A. baumannii, compared to S. aureus used presently. The authors feel a full antimicrobial study is required to assess gallium titanate as a candidate antimicrobial surface. Graphical abstract: Unlabelled Image Highlights: Gallium (9.4 at.%) can successfully ion-exchange with sodium (2.7 at.%) in titanate structures (0.5–1 μm deep). RHEED analysis was successfully conducted, for the first time, confirming d spacing values for titanate structures. Pre-heat-treated gallium titanate (2.76 ppm) released more gallium ions compared to post-heat-treated samples (0.68 ppm). Released gallium ion concentrations (4–40 μM) were significantly less than toxic concentrations for S. aureus (0.3–5.1 mM). Gallium titanate showed significant ( p <0.0001) cytotoxicity (76% cell viability reduction) vs. heat-treated layers (19% reduction).